Optimization of Green Ultrasound-Assisted Extraction of Carotenoids from Tagetes erecta L. using Natural Deep Eutectic Solvents (NADES) - Ni Luh Febby Andriani; Anak Agung Gede Rai Yadnya-Putra; Luh Putu Mirah Kusuma Dewi (Journal of Food and Pharmaceutical Sciences, 2026)
Carotenoids from marigold flowers (Tagetes erecta L.) are commonly extracted using conventional solvents like hexane and ethanol, which may pose environmental and health risks. Based on these considerations, this study aimed to evaluate the potential of Natural Deep Eutectic Solvents (NADES) as greener alternatives and to determine the optimal NADES composition and extraction conditions using Ultrasound-Assisted Extraction (UAE). The most effective NADES was selected based on total carotenoid content, statistically analyzed using one-way ANOVA. Optimization was carried out using Response Surface Methodology (RSM) with a Box–Behnken Design (BBD) to assess the effects of ultrasonic power, extraction time, and temperature. Total carotenoid content was determined by UV-Vis spectrophotometry. Among the tested solvents, the hydrophobic NADES composed of menthol:lactic acid (8:1) showed the highest efficiency (98.48 ± 0.20 mg β-carotene equivalent (BCE)/g dry sample (DS)), outperforming the hydrophilic NADES, hexane, and 80% ethanol. Optimization using Response Surface Methodology with a Box–Behnken Design identified optimal UAE conditions at 100% ultrasonic power, 40 minutes, and 60°C, yielding 304.01 ± 1.60 mg BCE/g DS. These results confirm the effectiveness of NADES as sustainable and efficient solvents for carotenoid extraction from marigold flowers.